Educar para a paz: combatendo a violência na escola - Nascimento, Carla Cristine Santos do (2015)
The theme of this paper is Educating for Peace: Combating Violence in the School. Violence is ever more present in all segments of society and inside the schools there exist various types of conflicts and tensions which can be characterized as acts of Bullying. However many schools negate the existence of this practice among the students or do not know of the existence of this problem. Frequently the aggressive behaviors among the students are not taken into consideration and are ignored by the teachers and by the school in general, however this type of behavior leads to serious individual and social consequences. To better present the research text, it was organized into three chapters: the first chapter presents a more theoretical discussion about the theme having as a title What is violence? where there is a confluence between the thinking of the researchers on the theme and the current context in which the school finds itself. The chapter also discusses the Concept of Violence, Violence and Society, Aggressiveness and Violence, the Different Forms of Violence, Spaces where violence occurs, Violence in the School, Education and Violence, Violence against the teacher. The second chapter emphasizes Violence and the Communal Interaction of the Student in the School highlighting the Bullying Phenomenon: Aggressive Behaviors among the Students. The unit also deals with what is Bullying, a history of the phenomenon of Bullying, School Bullying: the aggressor, the witnesses and the victims of Bullying. The third chapter explains the presence of ethical values in combating school violence in an attempt to educate for peace.